2004
DOI: 10.1094/phyto.2004.94.12.1368
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Among Potato virus Y Isolates Obtained from Potatoes Grown in the United States

Abstract: Potato field isolates (Solanum tuberosum) of Potato virus Y (PVY) collected from the midwestern and western United States were characterized using serological, molecular, and biological assays. PVY field isolates were grouped into the previously defined categories: PVY(O), European PVY(NTN), North American PVY(NTN), and PVY(N:O) recombinant and four previously undefined groups. Studies reported here agree with published reports from Europe and elsewhere in North America as PVY isolates capable of causing veina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 28 publications
4
57
1
5
Order By: Relevance
“…white burly. The observed typical external symptoms were leaf crinkle, mottling severe mosaic and stunting meanwhile, Piche et al (2004) reported that, 58 PVY field isolates transmitted to tobacco, 11 isolates produced a mild mosaic symptom and the remaining 47 field isolates induced varying degrees of leaf necrosis including venial necrosis, severe stunting and leaf death. An Indian PVY o common strain isolated from field-grown potato plants was maintained in N. glutinosa in an insect-free green-house (Gawande et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…white burly. The observed typical external symptoms were leaf crinkle, mottling severe mosaic and stunting meanwhile, Piche et al (2004) reported that, 58 PVY field isolates transmitted to tobacco, 11 isolates produced a mild mosaic symptom and the remaining 47 field isolates induced varying degrees of leaf necrosis including venial necrosis, severe stunting and leaf death. An Indian PVY o common strain isolated from field-grown potato plants was maintained in N. glutinosa in an insect-free green-house (Gawande et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…P1 gene, and known recombination junction sites of the PVY genome has led to the separation of isolates recovered from Europe from those isolated in North America (Piche et al, 2004 The Egyptian PVY isolate was clearly classified within group I and was more closely related to PVY NTN strains. Ten nucleotide substitutions resulted in 3 conserved amino acid substitutions resulted in 3 conserved amino acid substitutions (V 1 ® I, G 7 ® E, M or V and S 8 ® G) and were able to differentiate between both groups.…”
Section: Discussionmentioning
confidence: 99%
“…A primeira descrição da ocorrência desses subgrupos foi feita há mais de duas décadas, na Hungria (Beczner et al, 1984). Posteriormente sua ocorrên-cia foi relatada em vários outros países da Europa (Alemanha, Áustria, Bélgica, Dinamarca, França, Holanda, Polônia) (Beczner et al, 1984;Kerlan & Le Romancer, 1992;Kus;Steinbach & Hamann, 1989;van den Heuvel et al, 1994), no Líbano (Le Romancer et al, 1994), na América do Norte (Piche et al, 2004;Nie et al, 2004) e Japão (Oshima et al, 2000).…”
Section: Estadounclassified
“…PVY NTN pode induzir sintomas nos tubérculos de batata (Souza-Dias, 2001) na forma de anéis, letras e números, embora nem sempre exista uma associação direta, pois os tubérculos infectados podem permanecer assintomáticos (Singh et al, 2008). Sabe-se que o armazenamento de tubérculo-semente em câmara fria é um fator que aumenta a incidência dos sintomas em tubérculos (Fonseca, 2003 (Piche et al, 2004;Nie et al, 2004;Singh et al, 2008).…”
Section: Estadounclassified
See 1 more Smart Citation